The Eurasian spruce bark beetle Ips typographus shapes the microbial communities of its offspring and the gallery environment - Baños-Quintana, Ana Patricia; Gershenzon, Jonathan; Kaltenpoth, Martin (Frontiers in Microbiology, 2024)
The Eurasian spruce bark beetle (Ips typographus) is currently the most economically relevant pest of Norway spruce (Picea abies). Ips typographus associates with filamentous fungi that may help it overcome the tree's chemical defenses. However, the involvement of other microbial partners in this pest's ecological success is unclear. To understand the dynamics of the bark beetle-associated microbiota, we characterized the bacterial and fungal communities of wild-collected and lab-reared beetles throughout their development by culture-dependent approaches, meta-barcoding, and quantitative PCR. Gammaproteobacteria dominated the bacterial communities, while the fungal communities were mainly composed of yeasts of the Saccharomycetales order. A stable core of microbes is shared by all life stages, and is distinct from those associated with the surrounding bark, indicating that Ips typographus influences the microbial communities of its environment and offspring. These findings coupled with our observations of maternal behavior, suggest that Ips typographus transfers part of its microbiota to eggs via deposition of an egg plug treated with maternal secretions, and by inducing an increase in abundance of a subset of taxa from the adjacent bark.